2016
DOI: 10.3390/ph9030049
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, Safety, and Efficacy of Oral Administration of Extracts of Black or Red Maca (Lepidium meyenii) in Adult Human Subjects: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: The plant maca, grown at 4000 m altitude in the Peruvian Central Andes, contains hypocotyls that have been used as food and in traditional medicine for centuries. The aim of this research was to provide results on some health effects of oral administration of spray-dried extracts of black or red maca (Lepidium meyenii) in adult human subjects living at low (LA) and high altitude (HA). A total of 175 participants were given 3 g of either placebo, black, or red maca extract daily for 12 weeks. Primary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…It is possible that the perceived libido-enhancing of maca is due to its energising properties. The energising and antifatigue properties of maca have been investigated with promising results (Li et al, 2017, Gonzales-Arimborgo et al, 2016, Miao, 2015, Tang et al, 2017, Choi et al, 2012. Further investigation in this area is warranted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the perceived libido-enhancing of maca is due to its energising properties. The energising and antifatigue properties of maca have been investigated with promising results (Li et al, 2017, Gonzales-Arimborgo et al, 2016, Miao, 2015, Tang et al, 2017, Choi et al, 2012. Further investigation in this area is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…In a small pilot study, dyadic sexual desire increased in cyclists after 14 days treatment at 2000mg/day of an aqueous maca extract (Stone et al, 2009).This may suggest that the aphrodisiac properties are found in the aqueous extract of maca, explaining why the effect was noticed much earlier than with gelatinised maca but the sample was also very small, which decreases accuracy of results. Another larger cohort study of 175 participants treated with 3g of spray-dried maca over a period of 12 weeks showed only a modest increase in sexual desire with red maca relative to placebo (Gonzales-Arimborgo et al, 2016; See Appendix 4)…”
Section: Maca In Male Reproductive Health: Clinical Studiesmentioning
confidence: 99%
“…People consuming regular maca have a lower interleukin-6 level and higher health scores than those not consume it [1]. Although macamides content is higher in black maca, red one enhanced the health score of human suffered from chronic mountain illness [55]. It has been shown in women that postmenopausal symptoms such as anxiety, depression and sexual dysfunction are reduced without being dependent on reproductive hormones [56,57].…”
Section: Antioxidant Effects Of Maca As a Food Supplement In Human Numentioning
confidence: 99%
“…By scavenging DPPH and peroxyl radicals, polysaccharides isolated from maca have protected human erythrocyte against hydrogen peroxide and inhibited the hemolysis [62]. Some studies suggested that maca consumption is well tolerated and has no adverse effect [55]. On the contrary, some studies have reported negative effects on blood pressure [57,63,64].…”
Section: Antioxidant Effects Of Maca As a Food Supplement In Human Numentioning
confidence: 99%
“…Maca is used as food, and all studies with maca looking for biological activity have been performed through the oral route (Gasco, Aguilar, & Gonzales, ; Rubio et al., ; Yucra, Gasco, Rubio, Nieto, & Gonzales, ). This route in human has demonstrated to have high acceptability, it is safety and it has efficacy (Gonzales et al., ; Gonzalez‐Arimborgo, ). It is clear that in different investigations assessing products with systemic effects, the intraperitoneal route is preferred because it is an easy route of administration in experimental animals and this procedure avoids hepatic metabolism and a small amount of intraperitoneal injection may pass directly across the diaphragm and into the thoracic lymph (Abu‐Hijleh, Habbal, & Moqattash, ).…”
Section: Introductionmentioning
confidence: 99%